Legal Analysis of Predator Pricing Practices in Business Competition in the Digital Economy Era - Setiawan, Rahmat; Mustikowati, Endang (PT. Anagata Sembagi Education, 2025)
The rapid development of information and communication technology has changed the mechanism of business competition in the era of the digital economy, where digital companies use aggressive pricing strategies such as predatory pricing to eliminate competitors. Predator pricing, which is the setting of prices very low below production costs with the aim of weeding out competitors, is often disguised as a promotion or market acquisition strategy by large startups and digital platforms. This poses a major challenge in competition law enforcement in Indonesia because it is difficult to prove predatory intent and set very low price limits in the context of complex digital business models and limited cost transparency. Article 20 of Law No. 5 of 1999 normatively prohibits this practice, but its application is less adaptive to the characteristics of the digital economy. This study uses a normative juridical method with a study of regulations, ICC decisions, and international literature to examine the adequacy of legal norms related to predator pricing in Indonesia. The results of the study show the need to update regulations and increase the capacity of ICC in order to overcome market distortions due to predatory pricing strategies, especially those that have an impact on the sustainability of MSMEs. A multidisciplinary approach that integrates legal analysis, the digital economy, and data is ess.